Submarine Geomorphology and Glacimarine Sedimentary Processes Associated to Deglaciation in Europa Fjord, Chilean Patagonia - Rodrigo, Cristián; Cifuentes, Erick; Fernández, Rodrigo; Andrade, José; Rebolledo, Lorena; Muñoz, Diego; Muñoz, Práxedes (Frontiers in Marine Science, 2022)
In a period of high rates of glacier retreat, increasing meltwater discharge from tidewater glaciers can influence marine fjord ecosystems due to increase sediment delivery and accumulation rates in the proglacial environment. Glacier variations and associated changes in glacimarine processes are recorded in the sedimentary record and submarine geomorphology of fjords. In October-November 2017, CIMAR23 Cruise surveyed several fjords adjacent to the Southern Patagonian Icefield (SPI). In this study, we show detailed results of the multibeam bathymetry, backscatter and sub-bottom seismic profiles, and sediment core samples from Europa Fjord, located west of the central SPI area, to improve the analysis of the fjord glacial and sedimentary evolution and to connect its behavior with the other fjords in the region. For the cores 210Pb chronology, magnetic susceptibility, organic carbon, total nitrogen, and stable isotopes (δ13Corg, δ15N) were performed. The seafloor geomorphology showed that the most prominent submarine landforms are transverse morainal ridges, which indicate past stillstand glacier positions; these features formed during the deglaciation of the fjord (latest Pleistocene), and some, perhaps more recently during short episodic advance/retreat events. In the central and mouth fjord areas, erosional features such as lineations are found on the rocky bottom and interpreted as formed by past grounded glaciers. Several submarine moraines are generally well preserved, but some parts are crumbled by slope failures and erosion. Most of the seismic sections are interpreted as the expected subglacial-ice proximal-ice distal succession of facies, characteristic of single retreat environments. The sedimentary record includes bioturbed muds with muddy laminations and variable amounts of coarse sediments interpreted as ice rafted debris, suggesting a proglacial environment, punctuated by calving. From the beginning of the 20th century there is a tendency to an increase in the terrigenous organic material content, including an abrupt increase during the 80s-90s, and a decline in the last decade. This behavior is indicating possibly a general increase of surface terrestrial runoff and, for the last decade, an increase of glacial meltwater input which would be caused by an accelerated deglaciation.